8-Oxo-7,8-Dihydro-2′-Deoxyguanosine (8-oxodG) and 8-Hydroxy-2′-Deoxyguanosine (8-OHdG) as a Potential Biomarker for Gestational Diabetes Mellitus (GDM) Development - Sandra K. Urbaniak; Karolina Boguszewska; Michał Szewczuk; Julia Kaźmierczak-Barańska; Bolesław T. Karwowski (Molecules, 2020)
The growing clinical and epidemiological significance of gestational diabetes mellitus results from its constantly increasing worldwide prevalence, obesity, and overall unhealthy lifestyle among women of childbearing age. Oxidative stress seems to be the most important predictor of gestational diabetes mellitus development. Disturbances in the cell caused by oxidative stress lead to different changes in biomolecules, including DNA. The nucleobase which is most susceptible to oxidative stress is guanine. Its damage results in two main modifications: 8-hydroxy-2′-deoxyguanosineor 8-oxo-7,8-dihydro-2′-deoxyguanosine. Their significant level can indicate pathological processes during pregnancy, like gestational diabetes mellitus and probably, type 2 diabetes mellitus after pregnancy. This review provides an overview of current knowledge on the use of 8-hydroxy-2′-deoxyguanosineand/or 8-oxo-7,8-dihydro-2′-deoxyguanosine as a biomarker in gestational diabetes mellitus and allows us to understand the mechanism of 8-hydroxy-2′-deoxyguanosineand/or 8-oxo-7,8-dihydro-2′-deoxyguanosine generation during this disease.